TRAUMATIC EXPERIENCE IN NOVEL ABSOLUTE DARLING (2017) BY GABRIEL TALLENT - Nike Adenita; Anita sari (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This study focuses on the exploration of trauma in the novel My Absolute Darling (2017) by Gabriel Tallent, specifically examining how traumatic events affect characters and their development. The research aims to analyze the portrayal and effects of trauma as depicted in the narrative, utilizing Cathy Caruth's trauma theory (1995) as a theoretical framework to understand the psychological implications of traumatic experiences. Employing a qualitative research method, the analysis is presented in a written format, emphasizing the intricate details of the characters' experiences. The findings reveal that trauma stems from various forms of violent behavior, including physical, sexual, and verbal abuse. Additionally, the effects of trauma manifest as intrusive thoughts, anxiety, arousal, avoidance, cognitive and negative feelings. In a conclusion, the study provides a deeper understanding of how trauma shapes narratives and influences character interactions.